Sistem Informasi Administrasi Pengelolaan Barang Habis Pakai Di UPT Teknologi Informasi Dan Komunikasi Universitas Sebelas Maret Surakarta - Nugroho, Sigit; Pantjarani, Ari; Naury, Chairullah (Indonesian Journal of Information Technology and Computing (IMAGING), 2024)
Information systems are needed by an agency, both private and government agencies. Sebelas Maret University Surakarta (UNS) is a government agency engaged in higher education. Operational activities in each activity system at UNS require consumables, to manage data and information needed by students when attending lectures. Data recording of income, expenditure and stock of consumables at UPT Information and Communication Technology UNS still uses the manual method, using the Microsoft Excel application. Data recording of consumables and the current reporting process are considered less effective. This is because the initial process of data entry uses notes in the book and then it is copied to the Microsoft Excel application. A process like this takes a long time, besides that if you need last month's data you have to search one by one because the file is still random. Based on the description of the background, it can be formulated that the problem to be solved in this research is "How to design an administrative information system for the management of consumables at UPT Information and Communication Technology UNS". Limitations The problem that the author discusses in the study focuses more on the process of recording incoming goods, outgoing goods and stock of goods. The method used for system development uses the System Development Life Cycle (SDLC) with the Waterfall model. The programming language used is PHP Native and the database used is MySQL. With the design of the consumables management information system at the Information Technology and Technology Unit, it is expected to be able to present real time data reports.